IMPLEMENTATION OF THE PERATURAN PEMERINTAH NOMOR 9 TAHUN 2018 CONCERNING PROCEDURES FOR CONTROLLING THE IMPORT OF FISHERY COMMODITIES AND SALT COMMODITIES AS RAW MATERIALS AUXILIARY MATERIALS FOR INDUSTRY IN PAMEKASAN REGENCY - Mohammad Bustanol Husein; Fatoni Arif; Erina Saputri; Achmad Resa Fachrizi (DIA: Jurnal Administrasi Publik, 2021)
The Peraturan Pemerintah Nomor 9 Tahun 2018 concerning Procedures for Controlling Imports of Fishery Commodities and Salt Commodities as Raw Materials and Auxiliary Materials stipulates permits to import industrial salt. This study aims to provide an overview of the implementation of the Peraturan Pemerintah Nomor 9 Tahun 2018 concerning Procedures for Controlling Imports of Fishery Commodities and Salt Commodities as Raw Materials and Industrial Auxiliary Materials for Pamekasan Regency. This study uses a qualitative descriptive research design. Data collection techniques were carried out by interviews, and documentation. Findings in the field show that the implementation of this policy has an unfavorable impact because it cannot be felt by the target group, this can be explained by two variables of content of policy and context of policy which consists of 9 indicators, there are 6 indicators that show negative things, namely: interests affected there are 2 parties whose interests are influenced, namely salt farmers and local agencies, the type of benefits is less beneficial in the welfare of salt farmers because they do not understand the wishes of farmers, extent of change envisioned shows a less positive impact due to the lack of understanding of salt farmers on the salt land integration model, site of decision making this policy eliminates the authority of the KKP to determine the amount of import quotas, committed human resources with an average education level of salt farmers from elementary to junior high school. Financial resources, income earned by salt farmers are decreasing, policy compliance and responsiveness is not profitable for salt farmers, because the Government does not provide clear price standards, import quota restrictions are not adjusted to the needs of the recipient's location, and there are no clear rules on when to load and unload imported salt.